Patterns of variability in Azorella selago Hook. (Apiaceae) on sub-Antarctic Marion Island : climate change implications - Nyakatya, Mawethu Justice (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.